2021
DOI: 10.1172/jci.insight.150735
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2 activity on myeloid cells mediates immune suppression in the tumor microenvironment

Abstract: Angiogenesis, a hallmark of cancer, is induced by vascular endothelial growth factor-A (VEGF). As a result, anti-VEGF therapy is commonly employed for cancer treatment. Recent studies have found that VEGF expression is also associated with immune suppression in cancer patients. This connection has been investigated in preclinical and clinical studies by evaluating the therapeutic effect of combining anti-angiogenic reagents with immune therapy. However, the mechanisms of how anti-VEGF strategies enhance immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…VEGFR2 leads to the down-regulation of PD-L1 on myeloid cells. 130 Considering that PD-L1 expression on host bone marrow-derived cells is essential for the response to PD-L1 blockade, 189 our data suggest that anti-VEGF therapy might benefit from combination with immune checkpoint molecules other than PD-1/PD-L1. Indeed, we found that the efficacy of combining VEGF-specific blockade with anti-CTLA-4 antibodies is superior to combination with PD-1 blockade in a breast cancer syngeneic model.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…VEGFR2 leads to the down-regulation of PD-L1 on myeloid cells. 130 Considering that PD-L1 expression on host bone marrow-derived cells is essential for the response to PD-L1 blockade, 189 our data suggest that anti-VEGF therapy might benefit from combination with immune checkpoint molecules other than PD-1/PD-L1. Indeed, we found that the efficacy of combining VEGF-specific blockade with anti-CTLA-4 antibodies is superior to combination with PD-1 blockade in a breast cancer syngeneic model.…”
Section: Discussionmentioning
confidence: 85%
“…Vegfr2-deleted mouse model 130 colon cancer model. 106,130,131 Sunitinib inhibited MDSC recruitment via VEGFR inhibition and/or the inhibition of STAT3 in MDSCs.…”
Section: Mdscsmentioning
confidence: 99%
See 3 more Smart Citations